Soil carbon dynamics an integrated methodology - Bahn, Michael; Heinemeyer, Andreas; Kutsch, Werner 1960- (Cambridge University Press, 2009)
Carbon stored in soils represents the largest terrestrial carbon pool and factors affecting this will be vital in the understanding of future atmospheric CO2 concentrations. This book provides an integrated view on measuring and modeling soil carbon dynamics. Based on a broad range of in-depth contributions by leading scientists it gives an overview of current research concepts, developments and outlooks and introduces cutting-edge methodologies, ranging from questions of appropriate measurement design to the potential application of stable isotopes and molecular tools. It includes a standardised soil CO2 efflux protocol, aimed at data consistency and inter-site comparability and thus underpins a regional and global understanding of soil carbon dynamics. This book provides an important reference work for students and scientists interested in many aspects of soil ecology and biogeochemical cycles, policy makers, carbon traders and others concerned with the global carbon cycle.